GPU-accelerated lattice Boltzmann simulation of heat transfer characteristics of porous brick roof filled with phase change materials. (December 2020) - Luo, Zhuqing; Xu, Hongtao; Lou, Qin; Feng, Lingling; Ni, Jinpeng
Abstract: This paper presents a numerical study on the heat transfer characteristics of a porous brick roof filled with phase change materials (PCMs) in a typical day of June 2019 in Shanghai. Paraffin wax with different phase transition temperatures T m was selected as the PCM in the porous brick. A graphics processing unit (GPU)-accelerated multiple-relaxation time lattice Boltzmann method (MRT-LBM) was proposed owing to its good flexibility and parallel computing features. It was found that a lower T m resulted in a larger liquid fraction, and the PCMs with T m = 25 °C and 26 °C melted completely during the daytime. In the afternoon, the temperature gradient in the porous roof filled with PCM exceeded that of the roof filled with air, implying that PCMs have a significant thermal buffering capacity. In comparison with the traditional porous brick roof filled with air, the porous brick roof filled with PCM of T m = 27 °C performed best, and the heat flux during air-conditioning operation period was 67.8 kJ/m 2 and reduced by 73.4%. Therefore, the porous brick roof filled with PCM exhibited a significant improvement in the thermal inertia of the roof, and the energy consumption by the air-conditioning system could be reduced accordingly.